Molecular and pathobiological characterization of sixty one potato mop-top virus full-length cDNAs reveals great variability of the virus in the center of potato domestication, novel genotypes and evidence for recombination - Kalyandurg, P.; Gil, J.F.; Lukhovitskaya, N.I.; Flores, B.; Muller, G.; Chuquillanqui, C.; Palomino, L.; Monjane, A.; Barker, I.; Kreuze, Jan F.; Savenkov, E.I. (Wiley, 2017)
The evolutionary divergence of Potato mop-top virus (PMTV), a tri-partite, single-stranded RNA virus, is exceptionally low, based on the analysis of sequences obtained from isolates from Europe, Asia and North America. In general, RNA viruses exist as dynamic populations of closely related and recombinant genomes that are subjected to continuous genetic variation. The reason behind the low genetic variation of PMTV remains unclear. The question remains as to whether the low variability is a shared property of all PMTV isolates or is a result of the limited number of isolates characterized so far. We hypothesized that higher divergence of the virus might exist in the Andean regions of South America, the centre of potato domestication. Here, we report high variability of PMTV isolates collected from 12 fields in three locations in the Andean region of Peru. To evaluate PMTV genetic variation in Peru, we generated full-length cDNA clones, which allowed reliable comparative molecular and pathobiological characterization of individual isolates. We found significant divergence of the CP-RT and 8K sequences. The 8K cistron, which encodes a viral suppressor of RNA silencing, was found to be under diversifying selection. Phylogenetic analysis determined that, based on the CP-RT sequence, all PMTV isolates could be categorized into three separate lineages (clades). Moreover, we found evidence for recombination between two clades. Using infectious cDNA clones of the representatives of these two clades, as well as reassortants for the RNA-CP genomic component, we determined the pathobiological differences between the lineages, which we coined as S (for severe) and M (for mild) types. Interestingly, all isolates characterized previously (from Europe, Asia and North America) fall into the S-type clade, whereas most of the Peruvian isolates belong to the M-type. Taken together, our results support the notion of the single introduction of PMTV from the centre of potato origin to Europe, and subsequent spread of the S-type into Asia and USA. This is also supported by the suggested novel classification of isolates based on genetic constellations.